ASSESS THE COMPETENCE OF STUDENTS INDIVIDUAL METHODS OF DEVELOPMENT BASED ON PRACTICAL WORK IN THE SCIENCE OF THE INTERACTION OF RADIATION WITH MATTER IN HIGHER MEDICAL EDUCATION INSTITUTIONS - B. Z. Polvonov; E. Kh. Bozorov; B. S. Ruzimatova; M. Z. Khudoyberdieva (Scholars Digest Publishing, 2022)
This in the article student’s competence from physics practical exercises based on information important was one how much pedagogical technology and them application methods. This is provided in the article in this subject education process interactive technologies, virtual laboratories and other innovative approaches based on organization to grow methodology analysis is made. Also, in the article approaches based on students practical-processual competence development efficiency discussion will be done.
Keywords: Problem-based learning, microscope, blood, erythrocyte, interference, biological sample, medical physics, medical technology, pedagogical activities, creative thinking, radiation safety.